1975
DOI: 10.1093/nar/2.3.373
|View full text |Cite
|
Sign up to set email alerts
|

The secondary structure of E. coli ribosomes and ribosomal RNA's: a spearophotometric approach

Abstract: The thermal denaturation spectra of E. coli 50s and 30s ribosomal sub units and of their isolated RNA's were studied over the wavelength range of 2300-3000 Angstrom. It was possible to fit the experimental denaturation spectra with super positions of the reference spectra for denaturation of A - U and G - C base pairs derived from model polyribonucleotides. The coefficients of these linear combinations were used to calculate the fractions of A - U and G - C base pairs in the samples. It was found that the heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…From phosphorus determinations it was found that the large and the small subunits of Artemia ribosomes contain 40.8 (± 1) pg of RNA per A260 unit. It is satisfactory that the same value has been found for particles with different ratios of RNA to protein content, because the contribution of the proteins to the absorbance at 260nm is negligible (Araco et al, 1975;Elson et al, 1979). The same value can therefore be used for the complete ribosomes also.…”
Section: Results and Discussion Relation Between Absorbance And Concesupporting
confidence: 68%
“…From phosphorus determinations it was found that the large and the small subunits of Artemia ribosomes contain 40.8 (± 1) pg of RNA per A260 unit. It is satisfactory that the same value has been found for particles with different ratios of RNA to protein content, because the contribution of the proteins to the absorbance at 260nm is negligible (Araco et al, 1975;Elson et al, 1979). The same value can therefore be used for the complete ribosomes also.…”
Section: Results and Discussion Relation Between Absorbance And Concesupporting
confidence: 68%
“…strand DNA as compared with double strand DNA and ribosomal RNA. It is possible, however, that the lack of detectable binding to RNA was due to the known secondary structure of the ribosomal species used ( 17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The situation with respect to 16 and 23 S procaryote rRNAs is of course less clear, but similar in outline. That is, a high degree of secondary (and possibly tertiary) structure is inferred from optical denaturation experiments (Cox et al 1973;Araco et al 1975). Metastable alternative structured forms appear to exist depending on the presence or absence of Mg 2+ (Morris, Dahlberg & Dahlberg, 1975;Nisbet & Slayter, 1975), and this is true also of the precursor molecules (Slack, Sartirana & Loening, 1975).…”
Section: (B) Ribosomal Rnamentioning
confidence: 98%